O trabalho do enfermeiro em unidade de internação clínica cirúrgica sob a ótica da ergologia: um estudo de caso - Pinno, Camila (2016)
The work of nurse in a hospital environment is characterized by care, manage and administer various situations, disputes and problems that are part of this process; needing to use knowledge, involving the use of self / subjectivity to the effectiveness of the work process. So, it is questioned how occurs the nursing work in surgical clinic unit from the perspective of ergology? The study aimed to know the work of nurses in surgical clinical unit from the perspective of ergology. The specific objectives were to identify as occurs the prescribed work and real work of nurses in surgical clinic unit and identify as is the use of him by the nurse in surgical clinic unit. It is a qualitative research, type case study. The study site was an Adult surgical clinical unit of a university hospital in the RS. The data collection occurred from March to September 2015. The study participants were 12 nurses, working in surgical clinical unit for more than six months. The data collection was realized using the triangulation of data, consisting of documentary research, systematic observation and semi-structured interview. In the data analysis was used thematic analysis of Minayo. They were respected all ethical aspects according to Resolution 466 of December 2012 the National Health Council, and the project is approved by the Research Ethics Committee under number CAAE 41040815.9.0000.5346. After analyzing the data emerged the following thematic categories: 'Work of the nurse in Surgical clinical unit 'and' use of self during the work of nurse in surgical clinical unit. In the first category emerged specific aspects of the nursing work in relation to the prescribed work and real work, involving routine activities, Systematization of the nursing care, pre and post-operative guidelines, visit for the patients, standards and Operational Procedure Standard. The second category show characteristics from use of self for nurses during the work involving the use of self on specific priorities with the patient or with the team, development of activities / procedures, importance of 'knowledge' and acquired experience, autonomy of nurses and the use of self in the complications in Surgical clinical unit. Thus, it is concluded that the work is based on specific rules and routines, however the nurse makes use of self during the various activities developed, which is guided primarily in your knowledge, this enables greater autonomy in your work process.